2021
DOI: 10.1039/d1nr00038a
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of gut microbiota plays an important role in micro/nanoplastics-induced gut barrier dysfunction

Abstract: The widespread of microplastics (MPLs) and nanoplastics (NPLs), collectively abbreviated as M/NPLs, has markedly affected the ecosystem and become a global threat to human health. Multiple investigations have shown that...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(52 citation statements)
references
References 68 publications
4
47
0
1
Order By: Relevance
“…Thus, their potential effects on gut microbiota dysbiosis are an attractive proposal in need of verification. 28 It should be indicated that Drosophila has been proposed as a simple model to study the microbiome, 29 and perturbations of its microbiome can result in states of instability or disease in Drosophila. 30 The ingested PSNPLs can be subjected to interactions with midgut bacteria and with different intestinal enzymes, as well as with the acidic intestinal environment, potentially leading to decreases in their initial size; thereby, plastic particles can be eroded.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, their potential effects on gut microbiota dysbiosis are an attractive proposal in need of verification. 28 It should be indicated that Drosophila has been proposed as a simple model to study the microbiome, 29 and perturbations of its microbiome can result in states of instability or disease in Drosophila. 30 The ingested PSNPLs can be subjected to interactions with midgut bacteria and with different intestinal enzymes, as well as with the acidic intestinal environment, potentially leading to decreases in their initial size; thereby, plastic particles can be eroded.…”
Section: Discussionmentioning
confidence: 99%
“…Jin et al described the breakdown of the epithelial barrier, gut microbiota dysbiosis, and impacts on the metabolic pathways in the microbial community in mice treated with MP particles [ 29 ] ( Figure 4 ). At the same time, Li et al [ 30 ] and Qiao et al [ 217 ] characterized similar effects upon treatment with MP particles ( Figure 4 ). Strikingly, Zheng et al reported that MP administration aggravated acute DSS colitis and increased intestinal epithelial permeability [ 31 ].…”
Section: Global Plastic Crisis—intestinal Consequences?mentioning
confidence: 64%
“…Several studies describe adverse effects on the gut microbiome, reduced mucus secretion, and damage of barrier integrity upon administration of MP particles. Li et al describe the reduction in regulatory T-cells (Treg) and Th17 cells, increased Toll-like receptor 4 (TLR4) downstream signaling, and IL1α expression, suggesting activation of pro-inflammatory cascades and translocation of bacterial products into the system [ 28 , 29 , 30 , 31 , 32 , 217 , 218 ].…”
Section: Figurementioning
confidence: 99%
“…Some authors have hypothesized that MPs could carrier and release phthalate esters into intestinal traits with consequential toxic effects ( 108 ). Also, MPs also can induce GM dysbiosis and specific bacteria alterations ( 109 , 110 ). In the aquatic organism, MPs can affect the GM causing several harmful effects.…”
Section: Bidirectional Interaction Between Environmental Chemicals An...mentioning
confidence: 99%